The powerless intrinsic and extrinsic work motivation to affect grit and the innovative work behavior: Educational context - Encarnacion, Mary Joy; Magallanes, Theogenia; Mansueto, Jecel; Sallong, Mary Micah; Taloza, Gaudette Marie; Prado, Antonio (Divine Word International Journal of Management and Humanities (DWIJMH) (ISSN: 2980-4817), 2025)
The study aimed to examine the effect of individual work motivation on the employees' grit and innovative work behavior. To deepen the theories of the study, the literature was reviewed. The study used a descriptive assessment and correlational research design. The population of the study was all the employees of the Divine Word College of Loag. The data was gathered through research questionnaires. The study found that both intrinsic and extrinsic work motivation were not associated with employees' grit and innovative work behavior. Therefore, the hypothesis of the study is rejected. Another study should be conducted to include a broader population and take into account the contextual factors like organizational culture and leadership that might influence grit and innovative work behavior.